PEMBERIAN TEH KOMBUCHA PADA AIR MINUM TERHADAP NILAI LDL KOLESTEROL DAN HDL KOLESTEROL DARAH AYAM BROILER (Gallus sp) - Djaelani, Muhammad Anwar; Tana, Silvana (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2015)
The risk of consuming large quantities of food containing cholesterol has been widely known. By knowing the cholesterol content of food products, people could restrict their consumption of high cholesterol food. This study was to knew LDL cholesterol and HDL cholesterol of blood broiler chickens after treated with kombucha tea. This research used the CP 707 broiler strains chickens aged 1 week, treated with kombucha tea that has been fermented for 12 days at a temperature of 25oC. 20 broiler chickens devided into 4 treatment groups ( treated for 4 weeks), each group contain 5 replications. That group was : P0 as control group, drinking water without kombucha tea, P1 group with drinking water added with 10% kombucha tea, P2 group with drinking water added with 20% kombucha tea, P3 group with drinking water added with 40% kombucha tea. Variables measured were LDL cholesterol of blood chicken levels, HDL cholesterol of blood chicken levels and chicken drink consumption. Data were analyzed with Anova. The results showed that additional of kombucha tea in drinking water able to lower LDL cholesterol of blood chicken levels and able to increase HDL cholesterol of blood chicken levels significantly of broiler chickens. Keywords: broiler chickens, kobucha tea, cholesterol